The Effectiveness of the Knee-Chest Position in Midwifery Care for Correcting the Position of the Breech Presentation Fetus - Finta isti kundarti; Novalia Nur Aliza; Ira Titisari; Didien Ika Setyarini (Health and Technology Journal (HTechJ), 2025)
Breech presentation is an abnormal fetal position in which the buttocks or feet are located at the lower part near the birth canal, while the head is positioned above. This condition occurs in 3-4% of pregnancies and can increase the risk of delivery complications. The knee chest position is a non-invasive intervention that can help change the fetal position from breech to vertex (head down) through gravitational mechanisms and changes in pelvic space. This study aims to evaluate the effectiveness of the knee chest position in changing fetal position from breech presentation to vertex presentation in third-trimester pregnancy. This study used a case study approach with documentation of SOAP (Subjective, Objective, Assessment, Plan). The research subject was Mrs. LA at 32-33 weeks of gestational age, diagnosed with breech presentation. The knee chest position intervention was performed thrice daily for 15 minutes over 2 weeks with regular evaluations. After 2 weeks of knee chest position intervention, there was a change in fetal position from breech presentation to vertex presentation. Ultrasonographic evaluation showed successful fetal rotation without complications in either the mother or fetus. This study concludes that the knee chest position proved effective as a non-invasive intervention for managing breech presentation in third-trimester pregnancy. This research adds scientific evidence regarding the effectiveness of the knee chest position as a conservative management alternative before considering other medical interventions.